Intestinal piezo1 promotes neuroinflammation to facilitate oligodendrocyte ferroptosis post-traumatic brain injury - Jun, Ding Zhi; Liang, Wu; Xiong, Chen Zheng; Mao, Zeng Rui; Wang, Shangyuan; Zhang, Tang Ming (Penerbit Universiti Kebangsaan Malaysia, 2024)
The coexistence of traumatic brain injury (TBI) and cognitive impairment is increasingly common in clinical practice, but current research on identifying biomarkers for such conditions and precise intervention points is insufficient. This study utilized bioinformatics analysis with paired samples to explore potential causal links between inflammatory factors and TBI and cognitive impairment. By constructing a TBI model with Piezo1 gene knockout, we assessed the activation status of microglia in the brain, the differentiation process of oligodendrocyte precursor cells. The study identified a series of inflammatory factors significantly associated with TBI, including C-C motif chemokine 19, C-X-C motif chemokine 5, and interleukin-5. Bioinformatics analysis showed increased expression of CXCL10, CCL2, GNA15, NFKB1, and the top 5 key nodes were identified using the Cytohubba plugin. The experimental results indicated that the knockout of the Piezo1 gene significantly reduced the infiltration of microglia and neuroinflammation in the brain.